Remote working, technostress and well-being during Covid-19 - a gender perspective - Fuchs, Janine Joya (2022)
Using the JDR-model as a theoretical foundation and surveys as a practical foundation, this paper explores remote work characteristics, technostress, and employee well-being in the context of Covid-19.Gender differences within measures are highlighted in the individual contribution. An analysis of existing gender gaps in work contexts and gender norms during a crisis, demonstrate the topic's relevance. Significant differences were found in previous remote work experience (N= 425), with women having lesser compared to men, and professional isolation (N=407), with women feeling more professionally isolated. Using the study’s findings, recommendations are built and prioritized for companies and employees.